How should we treat May–Thurner syndrome and other causes of iliac vein obstruction? Examining the evidence. (February 2014) - Azarbal, Amir; Santo, Vincent; Moneta, Greg
May–Thurner syndrome most commonly refers to left-sided iliofemoral vein obstruction caused by compression of the left common iliac vein between the right common iliac artery and lumbar vertebrae. However, other forms of May–Thurner syndrome have been described, and May–Thurner syndrome is part of a larger spectrum of venous disease, iliac vein obstruction. May–Thurner syndrome and other forms of iliac vein obstruction can present with acute iliofemoral deep vein thrombosis or chronic venous symptoms of pain, swelling, skin changes and ulceration. The treatment of May–Thurner syndrome and other forms of iliac vein obstruction has evolved with the advancements of endovascular surgery.